Resposta de cultivares de trigo (Triticum aestivum L.) à interferência das plantas daninhas - Reinehr, Marcela (2013)
Weeds consist of the main type of direct interference with annual crops and are responsible for yield reduction. In this context , the objective of this research was to investigate the competitive ability of wheat cultivars with Italian ryegrass and radish weed plants. There were conducted works in the laboratory, field and in the greenhouse in 2012 and 2013. The article I includes laboratory and greenhouse experiments, where were evaluated the physiological quality of seeds of wheat cultivars and the effect of competition with weeds on germination and vigor of seeds, besides the maximum expression of their plant characteristics. In the article II there were evaluated coexistence among wheat cultivars BRS Guamirim, BRS 296, Fundacep Cristalino and Fundacep Raízes and Italian ryegrass and radish weeds. The articles III and IV show experiments developed in greenhouse, being the article III about to wheat ability in to compete with Italian ryegrass and radish weeds in a replacement series arrangement In the article IV is simulated the initial competition for light and the effects on the morphology of wheat plants, Italian ryegrass and radish. Thus, it is possible to conclude that the cultivar Fundacep Cristalino has the ability to maintain vigor of seeds when in competition throughout the cycle, besides to show morphological characteristics (plant height, leaf area, dry weight matter and high initial vigor), which confers superior competitive ability with weeds. The coexistence through the cycle with Italian ryegrass do not affect the yield of BRS Guamirim, BRS 296 , Fundacep Cristalino and Fundacep Raízes, however, the coexistence with radish affects significantly the PBA, ICA and yield components.Undependable of the competitor species, there are morphological alterations in the plants resulting from the initial competition for light.